Gender Dimension in Meaningful Public Participation: A Comparative Study of Village Regulation Formation in Indonesia and Poland - Dian Ratu Ayu Uswatun Khasanah; Rengga Kusuma Putra; Ani Purwanti; Satriya Nugraha; Edvardas Juchnevicius (Fakultas Hukum Universitas Muhammadiyah Sorong, 2026)
This study aims to analyze the gender dimension of meaningful public participation in the formulation of village regulations in Indonesia and Poland. Unlike previous studies, which generally addressed public participation, gender equality, or local governance separately and were limited to a single country, this study brings these three areas together in a cross-national comparison by assessing not only the presence of women but also their ability to influence decisions. The method of this study employs a qualitative approach with a normative-sociological comparative design. Secondary data in the form of legislation, scholarly articles, research reports, and policy documents were collected through a literature review and analyzed using document analysis, thematic analysis, and cross-national comparison. The novelty of this study lies in the development of a comparative framework linking four elements: legal guarantees, access to participation, women’s representation, and substantive influence on regulations. The results show that the legal frameworks of both countries have provided channels for local participation; however, provisions that tend to be gender-neutral have not yet guaranteed women’s substantive involvement. In Indonesia, village deliberations are more heavily influenced by social hierarchy, patriarchal norms, the dominance of the male elite, and women’s limited access to information and legal literacy, resulting in participation that is often merely procedural. In Poland, public consultations and local councils have more formal institutional structures and relatively more open access, but gender stereotypes and low representation of women in strategic positions still limit their influence on decision-making. Thus, the gap in Indonesia is primarily rooted in sociocultural barriers and participatory capacity, whereas the gap in Poland is more evident in political representation and institutional effectiveness. These differences underscore that legal recognition yields different qualities of participation when institutional contexts differ. This study concludes that meaningful participation requires gender-responsive consultation designs, the strengthening of women’s organizations, legal literacy, political education, affirmative action policies, and institutional support tailored to each country’s context.